Analysis of traffic density onthree-way junction in Jalan Sukabangun 2 using Vissim simulations model - Agusri, Erny; Arfan, Muhammad; Arfan, Muhammad (International Journal of Engineering and Technology, 2021)
VISSIM is a Simulations model which means a city traffic simulation model. VISSIM is a simulation software used by professionals to create simulations from dynamic traffic scenarios before making real plans. This research was conducted to determine how traffic performance and traffic performance optimization at the junctions between the existing conditions and the Vissim program caused by congestion. An effective method for overcoming non-jammed junctions can be made using the VISSIM method. This study was conducted at THREE-WAY JUNCTION in Jl. Sukabangun 2 (South) - Jl. R.A Abusamah (West) - Jl. Sukabangun 2 (Utara) - Jl. BeringinSukabangun 2 (East). In this study, three variations were used, namely the traffic light method, the method of forbidden turning right, and the method of dividing the road and turning signs. The results of PTV Vissim simulation showed that the traffic light method has a quite high queue length, namely 79m compared to the existing condition of 63m, for the vehicle delay in this method is 98.954s. On the method of forbidden turning right from the direction of Jl. BeringinSukabangun 2 (East) has a low queue length of 0.287m compared to the existing condition of 63m. The vehicle delay in this method is 13.307s. The method of dividing the road and turning signs, the queue length is quite low at 1.147m compared to the existing condition of 63m. The vehicle delay in this method is 30,169s. The results of the simulation revealed that the most effective method at THREE-WAY JUNCTION in jalanSukabangun 2 is method of forbidden turning right, dividing the roads and turning signs.Â Â